INTERACTIVE TECHNIQUES IN FOREIGN LANGUAGE LEARNING ONLINE IN NON-FORMAL EDUCATIONAL INSTITUTIONS IN CHINA - Gryzun, Liudmyla; Zhang, Caijing (The Modern Higher Education Review, 2024)
The article treats the currently important issues of foreign language mastering in China and the challenges of online English learning in terms of non-formal institutions. It is revealed the urgency of the research associated with the problems of dropping students’ motivation to learn foreign language, and the lack of a classroom environment that facilitates interactive and communicative language practice, which causes the necessity to find out efficient means of the students’ involvement into the interactive and practically driven forms of work. Minding the great potential of existing blended learning activities and interactive techniques, there was undertaken the attempt to engage the students of Chinese non-formal institutions in innovative foreign language practices during online classes. According to the goals of the work, it is explored and elaborated on how interactive techniques can be applied to enhance typical blended learning activities in online English learning as a second language. This study also provides detailed examples of interactive methods applied in Chinese non-formal institutions in terms of typical online learning activities. Besides, it offers a preliminary analysis of the impact of these techniques on students’ learning motivation. To get preliminary outcomes and test the prepared survey reliability, it was held in several groups of a Chinese private institution. In total 27 students of senior grades who learned English online in terms of implementation of various blended learning activities enhanced with interactive methods depicted above tool part in the survey. The acceptable reliability of the scales was proved. The outcomes of the survey, according to the levels of learners’ motivation are presented and discussed.